KOMPETENSI KEPRIBADIAN: INTEGRITAS, KETELADANAN, KEDEWASAAN, DISIPLIN, TANGGUNG JAWAB, STABILITAS EMOSI. - Riza Azka Fazila; Enda Fratiwi; Anna Sasa Sakinah; Fahmi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Education is an important process in developing quality human resources and strong character. In the educational process, teachers have a central role as educators, mentors, and role models for students. The success of learning is influenced not only by pedagogical competence, but also by teachers’ personality competence. This study aims to analyze the importance of teacher personality competence which includes integrity, exemplary behavior, maturity, discipline, responsibility, and emotional stability in supporting the learning process. This research used a qualitative approach with the type of library research. Data were collected through documentation techniques by reviewing books, scientific journals, articles, and previous relevant studies. The data were analyzed using the interactive analysis model of Miles, Huberman, and Saldaña, consisting of data reduction, data display, and conclusion drawing. The results of the study show that teacher personality competence has a significant influence on creating a conducive learning environment, increasing students’ learning motivation, shaping discipline, and developing positive character values. Teachers with good personality competence are able to become role models, maintain professionalism, and establish positive relationships with students. Therefore, the development of teacher personality competence needs continuous support through training, self-reflection, and institutional guidance to improve the quality of education.